KONTRIBUSI HUMAN INTIATIVE PADA PROGRAM INTIATIVE FOR EMPOWERMENT DALAM MENDUKUNG SUSTAINABLE DEVELOPMENT GOALS (SDGs) - Ahmad Darda (EMPATI: Jurnal Ilmu Kesejahteraan Sosial, 2024)
Abstract. The Government of Indonesia through Presidential Regulation Number 59 of 2017 concerning Implementation of Achieving Sustainable Development Goals, is committed that the implementation and achievement of SDGs is carried out in a participatory manner by involving all parties to improve people's welfare. Human Initiative as Non-Governmental Organizations (NGOs) engaged in social humanity has contributed through community empowerment programs in supporting the achievement of Sustainable Development Goals (SDGs) in Indonesia. This study aims to determine the contribution of the Human Initiative through the Nutrition Garden program in supporting the Sustainable Development Goals (SDGs). In this study the authors used a qualitative approach and data collection was obtained through interviews, observation, and documentation studies. The informants in this study were five people and were selected through a purposive sampling technique. The author uses the theory of stages of empowerment by Soekanto which states that in carrying out community empowerment, there are seven stages that must be passed. The results of this study indicate that the Human Initiative through the Nutrition Garden program in Tajurhalang Village has contributed to the three SDGs goals, the first of which is the first goal of No Poverty and Zero Hunger, and Good Health and Well Being. and Prosperous). Furthermore, the Human Initiative has also gone through the process and stages of community empowerment properly so that the Nutrition Garden program in Tajurhalang Village has been able to help beneficiaries with food security issues.Keywords: Community Empowerment, Sustainable Development Goals, Food Security. Abstrak. Pemerintah Indonesia melalui Perpres Nomor 59 Tahun    2017 tentang Pelaksanaan Pencapaian Tujuan Pembangunan Berkelanjutan, berkomitmen agar pelaksanaan dan pencapaian SDGs dilaksanakan secara partisipatif dengan melibatkan seluruh pihak untuk meningkatkan kesejahteraan masyarakat. Human Initiative sebagai Non-Governmental Organizations (NGO) yang bergerak di bidang sosial kemanusiaan memiliki andil melalui program pemberdayaan masyarakat dalam mendukung pencapaian Sustainable Development Goals (SDGs) di Indonesia. Penelitian ini bertujuan untuk mengetahui kontribusi Human Initiative melalui program Kebun Gizi dalam mendukung Sustainable Development Goals (SDGs). Pada penelitian ini, penulis menggunakan pendekatan kualitatif dan pengumpulan data diperoleh melalui proses wawancara, observasi, dan studi dokumentasi. Informan dalam penelitian ini sebanyak lima orang dan dipilih melalui teknik purposive sampling. Penulis menggunakan teori tahapan pemberdayaan oleh Soekanto yang menyatakan bahwa dalam melaksanakan pemberdayaan masyarakat, ada tujuh tahapan yang harus dilalui. Hasil penelitian ini menunjukkan bahwa Human Initiative melalui program Kebun Gizi di Desa Tajurhalang telah berkontribusi dalam tiga tujuan SDGs, yang pertama yaitu No Poverty (Tanpa Kemiskinan) dan Zero Hunger (Tanpa Kelaparan), dan Good Health and Well Being (Kehidupan Sehat dan Sejahtera). Selanjutnya Human Initiative juga telah melalui proses serta tahapan pemberdayaan masyarakat dengan baik sehingga program Kebun Gizi di Desa tajurhalang telah mampu membantu penerima manfaat dalam masalah ketahanan pangan.Kata Kunci: Pemberdayaan Masyarakat, Sustainable Development Goals, Ketahanan Pangan.